Physiological and Biochemical Responses to Heavy Metals Stress in Plants - Sarah Jorjani; Fatma Pehlivan Karakaş (International Journal of Secondary Metabolite)
Heavy metal (HM) toxicity is a severe abiotic stress that can cause significant harm to plant development and breeding, posing a challenge to sustainable agriculture. Various factors, including cellular toxicity, oxidative stress, osmotic stress, imbalance in the membrane, and metabolic homeostasis cause negative impacts on plant molecular, physiology and biochemistry. Some heavy metals (HMs) are essential micronutrients that play important roles in various plant processes, while excessive amounts can be harmful and have negative impacts on plant growth, metabolism, physiology, and senescence. Phytotoxicity with HMs and the deposition of reactive oxygen species (ROS) and methylglyoxal (MG), can lead to lipid peroxidation, protein oxidation, enzyme inactivation, DNA damage, and harm to other vital components of plant cells. Generally, HM toxicity as environmental stress led to response of plant with different mechanisms, first, the stimulus to external stress, secondly all signals transduction to plant cell and finally it beginning to find appropriate actions to mitigate the adverse stress in terms of physiological, biochemical, and molecular in the cell to survive plant. The purpose of this review is to better understand how plants respond physiologically and biochemically to abiotic HM stress.